KOMPETENSI PEGAWAI TERHADAP KINERJA PELAYANAN RUMAH SAKIT DI KOTA BANDUNG - Otang Soemantri; Sunandie Eko Ginanjar (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2022)
The focus of the research is to determine the effect of competence on the performance of hospital employees in the city of Bandung. The research methods used in the study are descriptive surveys and explanatory surveys. The type of investigation is causality, as well as time horizon, research is cross-sectional. The analytical techniques used consist of two types, namely, (1) descriptive analysis, especially for qualitative variables, and (2) quantitative analysis. Hypothesis testing using statistical tests. Quantitative analysis is emphasized to reveal the behavior of research variables, while descriptive qualitative analysis is used to explore the behavior of causative factors. The performance of nurses in Bandung City hospitals is considered good. Competence simultaneously affects the Performance of Nurses at Bandung City Hospital. But partially the dominant competence affects the performance of the Nurse, because competence more predominantly affects the performance, being the priority in improving the performance of the Nurse. They were enhancing the competence of nurses at Bandung City Hospital by including training and education, so that they are able to work more professionally.